Urinary exposure level of emerging chemicals in Chinese pregnant women and their associations with oxidative stress - Henglin Zhang; Yuxian Liu; Yanan Zhao; Jiye Zhang; Luhan Yang; Guanglan Zhang; Yanpeng Cai; Lan Yang; Jianya Xi; Ziliang Wang; Hong Liang; Maohua Miao; et al. (Emerging Contaminants)
Emerging chemicals (ECs), including parabens, bisphenols, bisphenol diglycidyl ethers, N,N′-substituted p-phenylenediamines, and benzotriazoles/benzothiazoles (BTH/BTRs), are widely used in industrial and consumer products. This study aimed to determine the urinary concentrations of 33 ECs and three oxidative stress biomarkers in pregnant women from a large birth cohort in Jiashan, China. Among the detected compounds, methyl paraben (MeP), bisphenol A (BPA), bisphenol A bis(2,3-dihydroxypropyl) glycidyl ether (BADGE·2H2O), N-isopropyl-N′-phenyl-1,4-phenylenediamine quinone (IPPDQ), and 1H-benzotriazole (1-H-BTR) were the most prevalent, with median concentrations ranging from 0.51 to 9.02 ng/mL. Notably, BTH/BTRs exhibited the highest exposure levels, approximately 4–16 times greater than those of other ECs. Most ECs showed elevated concentrations in pregnant women who were exposed to secondhand smoke prior to pregnancy. After model analysis, we found that mixtures of ECs were positively associated with both 8-hydroxy-2′-deoxyguanosine (8-OHdG) and 15(R)-prostaglandin F2α (15-PGF2α), while a negative trend was observed between ECs and 8-iso-prostaglandin F2α (8-PGF2α). Specifically, urinary benzyl paraben (BzP), BPA, bisphenol S (BPS), N-(1,3-dimethylbutyl)-N′-phenyl-1,4-phenylenediamine quinone (6PPDQ), IPPDQ, 2(3H)-benzothiazole (2-OH-BTH), and 2-methylthio-benzothiazole (2-Me-S-BTH) or 1-H-BTR were significantly (p < 0.05) associated with 8-OHdG. MeP, 6PPDQ, and 2-Me-S-BTH were linked to 15-PGF2α, while only bisphenol A (2,3-dihydroxypropyl) glycidyl ether (BADGE·H2O) showed a significant positive association with 8-PGF2α. This study provides a comprehensive evaluation of the exposure characteristics of ECs and their associations with oxidative stress biomarkers in pregnant women, offering new insights into the health risks associated with ECs exposure during critical periods of pregnancy.